(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Abstract Molinow Village is located in a coastal area in Tenga District, South Minahasa. The local fishermen face a common fishery problem with the fish caught that easily decomposed, so that the market value declined. It is, therefore, necessary to solve the problem through community dedication in applying an environmental friendly preservation to maintain the fish freshness. Nanochitosan is a nanotechnology based innovative product that extracted from fish scales as raw materials. In this program, the application of nanochitosan to several fish species was disseminated to the community target, those of fishermen wives associated with local women group. The target group was divided into 4 subgroups, each group was provided with several fish specimen to be sprayed with the nanochitosan solution and some other fish without nanochitosan. The fish condition was observed for three days in room temperature. The fish without nanochitosan were decomposed with many small insects surrounded, more than those with nanochitosan. Other organoleptic condition of decomposed fish was relatively different between the two treatments. Higher concentration of nanochitosan solution would be necessary for having more significant preservative effects to the raw fish. Community empowerment of the local fishermen to produce nanochitosan would be prospective program in the future.